The preamble to form-function mapping: The development of a theoretical construct to respond to elemental stages in the language-learner's processing of SE periphrastic verb forms [PowerPoint presentation] - Ibrahim Ali, Amina (My University, 2013)
This study set out to explicate, through a grounded-theory methodology, the ways in which learners (n=30) were negotiating the constituent parts of written Standard English (SE) periphrastic verb forms. The research questions were: 1) What sources of error are revealed by the methodological process of gathering and analysing periphrastic verb forms from formal and informal written assessments in the communicative ESL classroom where isolated focus on form is adopted? 2) How can these sources of error inform the creation of a theoretical framework with practical applicability that would redound to the benefit of grammar instruction, assessment and feedback? 3) What are the effects of text-bound instruction on the language-learning process? The explanatory theory concluded that learners were cognitively burdened. The operational theory set out to reduce: 1) intrinsic cognitive load, which emanated from the difficulty of the material to be learnt and 2) extraneous cognitive load, which resulted from weak instructional methods. An examination of written assessments generated from a group of learners (n=9) who benefitted from modifications to the instructional design showed that far more whole SE periphrastic verb forms were applied, the random application of forms was exceptional and approximations and lexical associations were fewer and not distributed in as many environments
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Language education; English as a Second Language; Language usage; Linguistics; Conference papers; Trinidad and Tobago